Factores asociados y su influencia en la neumonía en pacientes asilados en la unidad de cuidados intensivos en el Instituto Ecuatoriano De Seguridad Social De Babahoyo primer semestre 2018 - Caceres Reyes, Alexander (2018)
The present research work was carried out in the Ecuadorian Social Security Institute of Babahoyo during the First Period of 2018. Its objective is to identify the factors that affect pneumonia in the asylee patients of the intensive care unit, as well as to know the pathologies that are related as risk factors in the development of pneumonia. A descriptive and field study was carried out in which was composed of 45 patients admitted to the ICU ward of the Ecuadorian social security institute, which determined that 65% of the patients had pneumonia due to associated factors such as: fever, hypothermia, tachypnea, bradycardia, rhonchi, wheezing. Within the recommendations, handwashing was encouraged before and after handling patients, as well as disposing of antiseptic soaps or alcohol in gel, and using a mask when handling secretions. Within the proposal was implemented to design a prevention guide for the early identification of pneumonia risk factors in patients isolated from the ICU area.